Electrical characterization of single molecule and Langmuir–Blodgett monomolecular films of a pyridine-terminated oligo(phenylene-ethynylene) derivative - Osorio, Henrry Marcelo; Martín, Santiago; López, María Carmen; Marqués-González, Santiago; Higgins, Simon J.; Nichols, Richard J.; Low, Paul J.; Cea, Pilar (Beilstein Journal of Nanotechnology, 2015)
Monolayer Langmuir–Blodgett (LB) films of 1,4-bis(pyridin-4-ylethynyl)benzene (1) together with the “STM touch-to-contact” method have been used to study the nature of metal–monolayer–metal junctions in which the pyridyl group provides the contact at both molecule–surface interfaces. Surface pressure vs area per molecule isotherms and Brewster angle microscopy images indicate that 1 forms true monolayers at the air–water interface. LB films of 1 were fabricated by deposition of the Langmuir films onto solid supports resulting in monolayers with surface coverage of 0.98 × 10−9 mol·cm−2. The morphology of the LB films that incorporate compound 1 was studied using atomic force microscopy (AFM). AFM images indicate the formation of homogeneous, monomolecular films at a surface pressure of transference of 16 mN·m−1. The UV–vis spectra of the Langmuir and LB films reveal that 1 forms two dimensional J-aggregates. Scanning tunneling microscopy (STM), in particular the “STM touch-to-contact” method, was used to determine the electrical properties of LB films of 1. From these STM studies symmetrical I–V curves were obtained. A junction conductance of 5.17 × 10−5 G0 results from the analysis of the pseudolinear (ohmic) region of the I–V curves. This value is higher than that of the conductance values of LB films of phenylene-ethynylene derivatives contacted by amines, thiols, carboxylate, trimethylsilylethynyl or acetylide groups. In addition, the single molecule I–V curve of 1 determined using the I(s) method is in good agreement with the I–V curve obtained for the LB film, and both curves fit well with the Simmons model. Together, these results not only indicate that the mechanism of transport through these metal–molecule–metal junctions is non-resonant tunneling, but that lateral interactions between molecules within the LB film do not strongly influence the molecule conductance. The results presented here complement earlier studies of single molecule conductance of 1 using STM-BJ methods, and support the growing evidence that the pyridyl group is an efficient and effective anchoring group in sandwiched metal–monolayer–metal junctions prepared under a number of different conditions.
Keywords: Langmuir–Blodgett films; molecular electronics; STM touch-to-contact method